Development of Computer Accounting Applications with Microsoft Excel VBA (Macro) in The Preparation of Financial Statements of Micro, Small and Medium Enterprises (MSMES) Coconut Wood Furniture - Kaligis, Stevie; Walukow, Ivollety; Rengku, Jefrry (Publikasi Indonesia, 2023)
Micro, small and medium enterprises (MSMEs) are one of the economic activities carried out by most Indonesians. MSMEs have a very significant contribution in employment, forming Gross Domestic Product, national export value and national investment. Until 2019, the number of MSMEs in Indonesia reached 56.5 million. In this study, it found that the accounting information system was weak and not in accordance with Financial Accounting Standards at the Technical Education Training Center (BLPT) GMIM Kaaten Tomohon. Seeing the importance of accounting information systems today to the progress of business organizations, and the number of orders for goods at BLPT GMIM Kaaten Tomohon is currently increasing, a fast, accurate and accountable recording process is needed in order to make decisions appropriately based on Financial Accounting Standards. The purpose of this study is to help MSMEs develop the application of a Microsoft Excel VBA (Macro) based accounting information system on BLPT GMIM Kaaten Tomohon. The development method in this study uses the Borg and Gall Research and Development (R&D) model, through this model aims to produce a computer application-based Accounting information system. Data is obtained directly from the company through interviews and documentation. Based on the data obtained, it is stated that the BLPT GMIM Kaaten Tomohon accounting information system has several weaknesses, such as the non-implementation of a computer-based accounting information system. From these weaknesses, researchers provide advice to use a Microsoft Excel VBA (Macro) based accounting information system that is easy to operate and in accordance with SAK EMKM.